Monwabisi: a hydrodynamic study of the hazardous cell circulation and potential related solutions to a safer bathing facility - Kistner, Stephan (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.